Accessing health care in impoverished communities: The experiences of women living with hypertension and related conditions in the townships of Kwatsaduza, Gauteng province - Mashala, Cleopatra Matshidiso (Department of Social Development, 2025)
This study explores the experiences of women living with hypertension and related medical conditions in accessing healthcare services in the townships of Kwatsaduza in Gauteng. The objectives of the study are to: understand the effects of hypertension and related conditions on women living in poverty in Kwatsaduza; explore the impact of poverty on treatment adherence for hypertension and related conditions; explore the experiences of accessing healthcare services by women living with hypertension and related conditions in Kwatsaduza; and to examine how women cope with their diagnosis. The participants in the study received supplementary services from Itshudu Projects, an NGO that provides psychosocial and nutritional support to women living with hypertension and other health conditions. A qualitative research design and purposive sampling technique were implemented to recruit participants using the services of the organisation. Semi-structured one-on-one interviews were conducted to gather in-depth data from 20 participants. All participants were females aged between 18 and 35 who had been diagnosed with hypertension or a related medical condition, which included diabetes, hypertensive retinopathy, gestational hypertension, aneurysm, anxiety and obesity. The main findings of the study revealed that the diagnosis of hypertension and related conditions caused feelings of fear, stress, and self-blame. The study found that the required lifestyle changes that came with the diagnosis resulted in the participants losing close relationships with family and friends. In addition, the study found that the participants struggled to adhere to treatment due to lack of support from family and friends and inability to afford food. The study further revealed that while some participants had good experiences in the healthcare facilities, others received poor treatment and lack of confidentiality from nurses and doctors. The main recommendations are that there is a need for collaboration between individuals, families, and various government and non-government organisations in supporting women living with hypertension and related conditions in Kwatsaduza.